Multiscale MHD‐Kinetic PIC Study of Energy Fluxes Caused by Reconnection. Issue 3 (28th February 2020) - Lapenta, Giovanni; El Alaoui, Mostafa; Berchem, Jean; Walker, Raymond
Abstract: We present an analysis of the energy partitioning in the magnetotail during a substorm at 03:58:00 UT on 7 February 2009. The analysis employs a multiscale approach where we use a state from a global magnetohydrodynamics (MHD) model to spawn a kinetic particle‐in‐cell (PIC) simulation of a large portion of the tail. We directly investigate the energy fluxes resulting from magnetic reconnection. The kinetic run provides information on the additional processes absent in the MHD description. The ion bulk energy and enthalpy fluxes carry the greatest energy, but the Poynting flux and electron enthalpy flux also carry a significant portion. The other fluxes (e.g., heat flux) are relatively small but are especially important because they allow us to identify the extra processes present only in the kinetic description. The energy fluxes present in the MHD approximation (Poynting flux, enthalpy flux, and bulk energy flux) are quantitatively accurate, and the kinetic correction does not greatly alter the MHD picture. However, there are two unique effects resulting from the kinetic physics. First, the formation of a rarefaction of the plasma flow into the reconnection site leads to a progressive decline in time of the particle energy fluxes with respect to the Poynting flux. Second, we observe that the instabilities developing in the kinetic reconnection outflows form structures absent from the MHD description. These structures reveal themselves as fluctuations within the energy fluxes. Especially notable are regions of inverted heat flux, where the heat flux is in the opposite direction to the total energy and mass flow. Key Points: A multiscale approach provides information about kinetic processes missed by MHD in the description of the energy fluxes from reconnection Ion bulk energy and enthalpy flows carry the greatest fraction of the energy, a feature common to MHD and kinetic models A significant contribution to the energy budget comes from the electron enthalpy flux, an effect missed by MHD models